Brain Neurotransmitter Modulation by Gut Microbiota in Anxiety and Depression - Huang, Fei; Wu, Xiaojun (Frontiers in Cell and Developmental Biology, 2021)
Anxiety and depression are highly prevalent mental illnesses worldwide and have long been thought to be closely associated to neurotransmitter modulation. There is growing evidence that changes in the composition of the gut microbiota are related to mental health including anxiety and depression. In this review, we will focus on combining the intestinal microbiota with serotonergic, dopaminergic and noradrenergic neurotransmission in brain, with special emphasis on the anxiety- and depression-like behaviors in stress-related rodent models. Therefore, we reviewed studies conducted on germ-free rodents, or in animals subjected to microbiota absence using antibiotics, as well as via the usage of probiotics. All the results strongly support that the brain neurotransmitter modulation by gut microbiota is indispensable to the physiopathology of anxiety and depression. However, a lot of work is needed to determine how gut microbiota mediated neurotransmission in human brain has any physiological significance and, if any, how it can be used in therapy. Overall, the gut microbiota provides a novel way to altering neurotransmitter modulation in the brain and treating gut-brain axis diseases, such as anxiety and depression.